2008
DOI: 10.3742/opem.2008.8.1.032
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity and kinetic behavior of the Galgeuntang water extract

Abstract: SUMMARYGalgeuntang water extract exhibited a strong free radical scavenging activity and reducing power determination. However, a gradual increase in the free radical scavenging activity and reducing power determination was obtained with increasing concentrations. The highest radical scavenging activity was shown by the water extract from Galgeuntang (116.93 μg/mL) and the water extract from Cinnamonum cassia Presl. (95.01 μg/mL). These results of phenolic and flavonoid contents of the extracts indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…GGWE is a traditional herbal decoction that has been used to treat common cold, fevers, and inflammatory diseases in China, Japan, and Korea [ 10 , 23 ]. Experimental studies have revealed that GGWE has anti-viral, anti-allergic, antioxidant, and antiadipogenic effects [ 13 , 14 , 15 , 24 , 25 ]. Furthermore, GGWE was shown to reduce inflammatory mediators such as inflammatory cytokines, iNOS, and NF-κB expression through the inhibition of NF-κB in LPS-stimulated microglial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GGWE is a traditional herbal decoction that has been used to treat common cold, fevers, and inflammatory diseases in China, Japan, and Korea [ 10 , 23 ]. Experimental studies have revealed that GGWE has anti-viral, anti-allergic, antioxidant, and antiadipogenic effects [ 13 , 14 , 15 , 24 , 25 ]. Furthermore, GGWE was shown to reduce inflammatory mediators such as inflammatory cytokines, iNOS, and NF-κB expression through the inhibition of NF-κB in LPS-stimulated microglial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that GGWE attenuated inflammatory responses in lipopolysaccharide (LPS)-stimulated BV-2 microglial cells via inhibition of the NF-κB pathway [ 12 ]. In another study, GGWE exhibited a strong free radical scavenging activity [ 13 ]. In mouse studies, GGWE exhibited therapeutic efficacy in influenza virus infected mice.…”
Section: Introductionmentioning
confidence: 99%
“…According to Korean Herbal Pharmacopoeia (2013), puerarin, ephedrine, paeoniflorin, glycyrrhetic acid, and (6)-shogaol are confirmed as marker compounds of GGT. As a result of its anti-inflammatory, anti-pyretic, analgesic [2], antioxidant [3], and anti-influenza virus [4] activities, GGT has been used to treat the common cold. In addition, GGT has been reported to modulate atopic dermatitis [5] and chronic rhinosinusitis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the traditional herbal formulas, Galgeun-tang (GGT, gegen tang, kakkon-to), Gumiganghwal-tang 4,5) These herbal formulas composed of different crude herbs (Table 1) and commonly exhibits various biochemical activities such antipyretic [6][7][8][9][10][11] and anti-inflammatory 12) effects in common. In addition, GGT has antioxidant 13) and antivirus 14) effects, and SSE and SCRT have antiallergic 15) and antiasthma 16) effects. SCRT also exhibits biological activities such as antiobesity and improvement of lung damage 16) as well as induction of CYP2B, CYP2C and CYP3B activation effects.…”
Section: Introductionmentioning
confidence: 99%